Agent-relative consequentialism and collective self-defeat - HAMMERTON, Matthew (Institutional Knowledge at Singapore Management University, 2020)
Andrew Forcehimes and Luke Semrau argue that agent-relative consequentialism is implausible because in some circumstances it classes an act as impermissible yet holds that the outcome of all agents performing that impermissible act is preferable. I argue that their problem is closely related to Derek Parfit's problem of ‘direct collective self-defeat’ and show how Parfit's plausible solution to his problem can be adapted to solve their problem.